Allogeneic stem cell transplantation in fully MHC-matched Mauritian cynomolgus macaques recapitulates diverse human clinical outcomes - Benjamin J. Burwitz (Nature Portfolio, 2017)
Rhesus macaques are not ideal for studying response to allogeneic hematopoietic stem cell transplant (allo-HSCT) owing to complex MHC genetics that prevent full MHC-matching. Here the authors show that inbred Mauritian-origin cynomolgus macaques are a superior preclinical model of allogeneic stem cell transplantation that mimics diverse clinical outcomes of human allo-HSCT.